Migration Routes and Stopover Sites of Upland Geese Chloephaga Picta in South America. (May 2018) - Pedrana, Julieta; Pütz, Klemens; Bernad, Lucía; Pon, Juan Pablo Seco; Gorosabel, Antonella; Muñoz, Sebastián D.; Isacch, Juan Pablo; Matus, Ricardo; Blank, Olivia; Lüthi, Benno; Lunardelli, Melina; Rojas, Pablo
The Upland Goose (Chloephaga picta picta) is a migratory species of South America, which breeds from September to April in Patagonia (Argentina and Chile) and winters from May to September in the southern Pampas (Argentina). Despite some protection in both countries, this species is still persecuted and large numbers are killed by unregulated hunting. Therefore, precise knowledge of their migratory routes is vital to ensure protection of necessary resources and sites throughout the year. We deployed five miniaturised satellite transmitters on adult Upland Geese to gather data about breeding, wintering and stopover sites all along their migratory routes. We aimed to identify important areas in the wintering and breeding grounds through kernel density analyses, and to match these sites along the migration routes with protected areas. Tracked birds exhibited different migration routes and reached different breeding grounds. Two individuals travelled from their wintering grounds in Buenos Aires province to their presumed breeding areas in southern Patagonia. However, we also found different stopover sites from another bird in northern Patagonia, from the ones postulated before, and evidence that some Upland Geese are not large-scale migrants. Our results highlight a considerable amount of plasticity in Upland Geese migratory behaviour. This study represents an essential first step towards identifying important stopover sites along the Upland Geese flyways and it also highlights the lack of protected habitats along most of their migration routes.